The Bethesda System for Reporting Cervical Cytology : Definitions, Criteria, and Explanatory Notes - Nayar, Ritu; Wilbur, David C. (Springer International Publishing : Imprint: Springer, 2015)
This book offers clear, up-to-date guidance on how to report cytologic findings in cervical, vaginal and anal samples in accordance with the 2014 Bethesda System Update. The new edition has been expanded and revised to take into account the advances and experience of the past decade. A new chapter has been added, the terminology and text have been updated, and various terminological and morphologic questions have been clarified. In addition, new images are included that reflect the experience gained with liquid-based cytology since the publication of the last edition in 2004. Among more than 300 images, some represent classic examples of an entity while others illustrate interpretative dilemmas, borderline cytomorphologic features or mimics of epithelial abnormalities. The Bethesda System for Reporting Cervical Cytology, with its user-friendly format, is a "must have" for pathologists, cytopathologists, pathology residents, cytotechnologists, and clinicians.